2021
DOI: 10.3389/fcimb.2021.712381
|View full text |Cite
|
Sign up to set email alerts
|

Moderate-Intensity Physical Exercise Affects the Exercise Performance and Gut Microbiota of Mice

Abstract: The gut microbiota is closely associated with the health of the host and is affected by many factors, including exercise. In this study, we compared the gut microbial changes and exercise performance over a 14-week period in mice that performed exercise (NE; n = 15) and mice that did not perform exercise (NC; n = 15). Mice were subjected to stool collection and exercise tests one week prior to adaptive training and after 2, 6, 10, and 14 weeks of exercise. Bacteria associated with the stool samples were assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 46 publications
(52 reference statements)
1
19
0
Order By: Relevance
“…On this note, it is worth underlining that the experiments reported in this manuscript were obtained by carefully crossing heterozygous mice and that experiments were also repeated with the progeny of new Obscn KO founders, kindly provided again by Dr. Ju Chen at the University of California, San Diego. Moreover, we cannot rule out the possibility that additional events, including changes in the diet which may affect mice microbiota, may have contributed over the years to modify the mouse phenotype [59]. All in all, we are rather inclined to explain the changes in the running ability of the Obscn KO mice as some sort of adaptation.…”
Section: Discussionmentioning
confidence: 92%
“…On this note, it is worth underlining that the experiments reported in this manuscript were obtained by carefully crossing heterozygous mice and that experiments were also repeated with the progeny of new Obscn KO founders, kindly provided again by Dr. Ju Chen at the University of California, San Diego. Moreover, we cannot rule out the possibility that additional events, including changes in the diet which may affect mice microbiota, may have contributed over the years to modify the mouse phenotype [59]. All in all, we are rather inclined to explain the changes in the running ability of the Obscn KO mice as some sort of adaptation.…”
Section: Discussionmentioning
confidence: 92%
“…The difficulty in making general recommendations is that it was rare to find a physical activity paper within our search criteria that controlled for diet [ 31 , 131 ]. Animal studies demonstrate that exercise performance and conditioning that takes place in long-term interventions have positive effects on both the microbiome and host metabolism [ 145 ]. Transferring this model to human studies will prove challenging because of the need to maintain a controlled research diet over the length of the study.…”
Section: Discussionmentioning
confidence: 99%
“…In 2018, researchers from the Mayo Clinic found that overweight adults were more likely to successfully lose weight if they had a higher abundance of Phascolarctobacterium [ 21 ]. In addition to its role in energy metabolism [ 22 ], Phascolarctobacterium could reduce the availability of luminal succinate and therefore prevent the growth of Clostridioides difficile in the human body, which could cause severe intestinal inflammation [ 23 ]. Ruminococcaceae is another beneficial bacterium that can maintain human digestive function and reduce the risk of gastrointestinal tumor growth.…”
Section: Discussionmentioning
confidence: 99%